Moratorium from Shariah Perspective: Its Impact on Islamic Banking in Malaysia - Ali, Mohammad Mahbubi (Ekonomi Islam Indonesia, 2024)
As the COVID-19 pandemic intensifies worldwide, lockdowns-or partial lockdowns-to restrict movement have been the preferred mechanism to reduce the infection rate of the virus in most countries. Imposing a movement control necessitates the closure of economic and business activities, including restricting travel between borders. Malaysia, for instance, implemented the Movement Control Orders (MCO) beginning March 18, 2020. Nevertheless, this measure caused many businesses to shut down and impacted millions of individuals' cash flow, small and medium enterprises, and corporate sectors. In response, many governments introduced the repayment moratorium policy to ease the cash flow of SMEs and individuals affected by the COVID-19 pandemic. This article aims to examine the repayment moratorium from an Islamic perspective. It also sheds critical light on the impact of COVID-19 and moratorium policies on the Islamic banking industry in Malaysia and other jurisdictions. The study is qualitative, adopting library research, benefiting from various sources: the Qur'an, the Prophet's tradition, the opinions of Shari'ah scholars and other available secondary data. This study should serve as a reference point for academics, policymakers, and researchers interested in the moratorium issue in Islamic finance.